Market policies in the public construction of citizenship - Espejo Villar, L. Belén (Education Policy Analysis Archives, 2018)
The aim of this study is to show the existence of two differentiated lines of action underlying the bases of citizenship according to how it takes place in the social context, or as a point of interest in education, in both cases promoting different organizational models that lead to divergent constructions of citizenship. Analysis of a set of selected elements shows a plural idea of citizenship that in some cases responds to political paradigms of educational governance that insist on reinforcing the governing capability of the actors by shaping a citizenry more competent in terms of employability and independence. In contrast, in social contexts we are witnessing a hollowing out of meaning of the concept of citizenship as defined by Marshall and Bottomore (1998), the result of policies that have delegated responsibilities to sectors that have gradually been losing their political function in the control and management of social capital. The diversification of the discourses underlying the conceptualization of the notion of autonomy is giving more power to educational institutions by unblocking projects of citizen participation to achieve a more active citizenship. At the same time that some educational policies are expanding towards democratic developments, others are becoming polarized towards a level of autonomy underlying which is a notion of citizenship ever more subjected to market dictates whose premises are fostering educational systems forged in the culture of entrepreneurship. In addition to the educational context, it is necessary to interpret the individualism and assistentialism (welfare) on which a new political subject would emerge in the social context, without disparaging the expectations that social movements are generating inasmuch as supports for community models of organization and construction.